Morphological Analysis on Affixes Found in Song Lyrics Composed by Taylor Swift - Manalu, Sri Hartati Nelvi; Purba, Resperdiana (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This research aims to analyze the types of affixes found in Taylor Swift's song lyrics in the album